Praktis Seni Video Eksperimental Dalam Konteks Seni Tampak Tempatan - Melcom, Angkun (2016)
Experimental video art is the advancement of video art platform and be part of the development of the visual arts since 1960s. The understanding was referring to a formation or production of artwork using technological tools and video technology as an artistic medium. The emergence of the experimental video art practices in the local visual arts scene, directly havevarious impact. It should be understood in the context of the visual arts and not as other medium. Therefore, this research is intended to document the impact of the practical development of experimental video art and explain the potentiality of video art as a medium in the production of artwork. In addition, this research also is to identify the characteristic of experimental video art practices in the context of Malaysian visual art scene. The research methodology that use in this research is fully qualitative and case study. The method is use to collect data and information that needed to achieve the research objective and answer the research question in the early chapter of the research. This is because the research design of this research is not experimental, that is this research using verbal and description method to collect the data also information. In the other hand, the type of case study that use in this research is instrumental case study, it’s content three collecting data method such as observation, documentation and in-depth interview.